Corporate Hexes: The Conundrum of Bound Leaders in Shakespeare’s The Tragedy of Macbeth - Özdemir, Ömer (Journal of History Culture and Art Research, 2024)
Shakespeare’s stage in Macbeth is red. It is a vivid and bloody reminder of the power and violence that comes with hubristic behaviour and sheer ambition. It serves as a warning for those who have their sights set on leadership, depicting a dark and contradictory view of how violence, as a means to exert dominance and maintain control, consumes the souls of the leaders. In the play, violence is both a tool of oppression and a form of justice, a point that is made even more poignant by its relevance to modern-day politics. In the contemporary world of politics, corporate influence, particularly in Anglo-American context for the current study, leaders frequently become susceptible to external forces, motivated by ambition and paranoia. Similarly, Macbeth’s story serves as a reminder that no one is immune to the seduction of power. It mirrors contemporary issues and challenges in modern-day politics asserting that no matter what the system of governance is, leaders fall prey to the incantations of the unseen powers. Hence, in the study the writer seeks to explore an intersection of history and present-day power relations under corporate influence in an Anglo-American context.